Helix Nucleation by the Smallest Known α‐Helix in Water. (25th May 2016) - Hoang, Huy N.; Driver, Russell W.; Beyer, Renée L.; Hill, Timothy A.; D. de Araujo, Aline; Plisson, Fabien; Harrison, Rosemary S.; Goedecke, Lena; Shepherd, Nicholas E.; Fairlie, David P.
Abstract: Cyclic pentapeptides (e.g. Ac‐(cyclo‐1, 5)‐[KAXAD]‐NH2 ; X=Ala, 1 ; Arg, 2 ) in water adopt one α‐helical turn defined by three hydrogen bonds. NMR structure analysis reveals a slight distortion from α‐helicity at the C‐terminal aspartate caused by torsional restraints imposed by the K( i )–D( i +4) lactam bridge. To investigate this effect on helix nucleation, the more water‐soluble2 was appended to N‐, C‐, or both termini of a palindromic peptide ARAARAARA (≤5 % helicity), resulting in 67, 92, or 100 % relative α‐helicity, as calculated from CD spectra. From the C‐terminus of peptides, 2 can nucleate at least six α‐helical turns. From the N‐terminus, imperfect alignment of the Asp5 backbone amide in2 reduces helix nucleation, but is corrected by a second unit of2 separated by 0–9 residues from the first. These cyclic peptides are extremely versatile helix nucleators that can be placed anywhere in 5–25 residue peptides, which correspond to most helix lengths in protein–protein interactions.